"Good morning, COVID!" the inertia of journalistic imaginaries in morning shows' online comments. (December 2022) - Gutsche, Robert E; Forde, Sydney L; Pinto, Juliet; Zhu, Yanqi
This textual analysis examines meanings of user comments to Facebook posts of three UK breakfast programs as COVID-19 entered England in 2020. This analysis suggests that during this time of crisis and uncertainty, users' – even if trolling, interacting through incidental media use, or commenting as regular contributors to the pages – relied on traditional and lasting interpretations of conventional journalistic standards in their discourse surrounding "soft news" content. We argue that such comments represent an "inertia" of longstanding journalistic imaginaries that have survived an increased hybridity of news.